El relato europeo de Felipe González en la transición a la democracia : un estudio de narrativa digital - Carlos Sanz Díaz; Antonio Moreno Juste (Amnis)
Any analysis of the digital narrative around the topic of Spain as a part of Europe has one of its most qualified exponents in the figure of Felipe González, whose career as a national political leader acquires its authentic dimension in the field of European integration, as corresponds to one of the protagonists of the great European cavalcade of the 80s and 90s. González also represents the canonical narrative that emerged during the Democratic Transition, a story of the reunion between Spain and Europe that is embedded in a pragmatic reflection on the future of Europe as a program of political action. Digital media, and especially those deposited in the Felipe González Foundation, allow us both to analyze this narrative and to reflect on the discursive strategies used by political actors in the politicization of "Europe."